Sport policy and transformation in small states: New Zealand's struggle between vulnerability and resilience - Sam, M. P. (International Journal of Sport Policy and Politics, 2015)
Small states are broadly distinguished on economic, political and cultural grounds and more particularly in relation to their vulnerability and resilience. This paper examines how legitimations around a country`s small size can induce compromises to buttress particular sport policies. Drawing from the New Zealand context, it explores how domestic cooperation can be prompted by the discursive frames of smallness itself. It further suggests that New Zealand`s corresponding ambition to `punch above its weight` has enabled policy transformations to make the sport system appear more legitimate but no less vulnerable. Because scale invites consolidation, targeting and rationing, central sport agencies in small states may have to paradoxically invoke strategies to break the very communal bonds that provide them with the `fertile` conditions for growth and competitive advantage. The study of small states may help scholars and policy-makers to better understand the significance of `managed intimacy` as a counterbalance to neoliberal doctrines.